The hunger of the gods eaudiobook - Gwynne, John (The Bloodsworn Trilogy, 2022)
Set in a Norse-inspired world and packed with myth, magic, and vengeance, this epic saga follows a band of warriors as they face the wrath of ancient gods and change the shape of the world. Lik-Rifa, the dragon god of legend, has been freed from her eternal prison. Now she plots a new age of blood and conquest. As Orka continues the hunt for her missing son, the Bloodsworn sweep south in a desperate race to save one of their own–and Varg takes the first steps on the path of vengeance. Elvar has sworn to fulfil her blood oath and rescue a prisoner from the clutches of Lik-Rifa and her dragonborn followers, but first she must persuade the Battle-Grim to follow her. Yet even the might of the Bloodsworn and Battle-Grim cannot stand alone against a dragon god. Their hope lies within the mad writings of a chained god. A book of forbidden magic with the power to raise the wolf god Ulfrir from the dead . . .and bring about a battle that will shake the foundations of the earth. Praise for The Shadow of the Gods "There is not a dull chapter in this fantasy epic." —Vulture (Best of the Year) "A satisfying and riveting read. It's everything I've come to expect from a John Gwynne book." —Robin Hobb "A masterfully crafted, brutally compelling Norse-inspired epic." —Anthony Ryan "A masterclass in storytelling . . . epic, gritty fantasy with an uncompromising amount of heart." —FanFiAddict For more from John Gwynne, check out: The Bloodsworn Trilogy The Shadow of the Gods Of Blood and Bone A Time of Dread A Time of Blood A Time of Courage The Faithful and the Fallen Malice Valor Ruin Wrath